Improving the Performance and High‐Field Stability of FAPbBr3 Single Crystals in X‐Ray Detection with Chenodeoxycholic Acid Additive (Small Methods 4/2023). Issue 4 (20th April 2023) - Jiang, Wei; Ren, Jiwei; Li, Haibin; Liu, Dan; Yang, Lijun; Xiong, Ying; Zhao, Yiying
Abstract : Inside Front Cover In article number 2201636, Yiying Zhao and co‐workers demonstrate that chenodeoxycholic acid as additive can ionize the hydrogen ions and thus the decomposition of FA ions is suppressed in precursors, leading to better stoichiometry of FAPbBr3 single crystals. Meanwhile, the chenodeoxycholic acid can coordinate with Pb atoms and assist FAPbBr3 single crystal growth, resulting in a better crystal orientation.